Omnium annalium monumenta : historical writing and historical evidence in Republican Rome - Sandberg, Kaj 1965-; Smith, Christopher John, 1965- (Historiography of Rome and Its Empire, 2017)
This edited volume brings a variety of approaches to the problem of how the Romans conceived of their history, what were the mechanisms for their preservation of the past, and how did the Romans come to write about their past. Building on important recent work in historiography, and the recent memory turn, the authors consider the practicalities of transmission, literary and generic influences, and the role of the city of Rome in preserving and transmitting memories of the past. The result is a major contribution to our understanding of the role history played in Roman life, and the kinds of evidence which could be deployed in constructing Roman history.